2015
DOI: 10.1016/j.expneurol.2014.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory function after selective respiratory motor neuron death from intrapleural CTB–saporin injections

Abstract: Amyotrophic lateral sclerosis (ALS) causes progressive motor neuron degeneration, paralysis and death by ventilatory failure. In rodent ALS models: 1) breathing capacity is preserved until late in disease progression despite major respiratory motor neuron death, suggesting unknown forms of compensatory respiratory plasticity; and 2) spinal microglia become activated in association with motor neuron cell death. Here, we report a novel experimental model to study the impact of respiratory motor neuron death on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
54
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(63 citation statements)
references
References 59 publications
9
54
0
Order By: Relevance
“…The lack of evident functional impairment using EMG during ventilatory behaviors suggests that assessment of higher force behaviors (i.e., airway occlusion or sneezing) and normalization to maximum force may be needed to reveal a change in EMG amplitude after partial injuries to the phrenic motoneuron pool as seen after spinal cord contusion or other models of toxic motoneuron death. 58 Overall, these results are consistent with a large reserve capacity for ventilatory functions of the diaphragm muscle.…”
Section: Minimal Functional Impairment After Unilateral Midcervical Csupporting
confidence: 72%
“…The lack of evident functional impairment using EMG during ventilatory behaviors suggests that assessment of higher force behaviors (i.e., airway occlusion or sneezing) and normalization to maximum force may be needed to reveal a change in EMG amplitude after partial injuries to the phrenic motoneuron pool as seen after spinal cord contusion or other models of toxic motoneuron death. 58 Overall, these results are consistent with a large reserve capacity for ventilatory functions of the diaphragm muscle.…”
Section: Minimal Functional Impairment After Unilateral Midcervical Csupporting
confidence: 72%
“…Five sections at the C 4 –C 5 segmental level from each rat in each group were used for immunohistochemical analyses conducted by a blinded investigator. Location of putative phrenic motor neurons in the ventral horn was validated based on diagrams from The Spinal Cord (Watson et al 2009) and extensive experience in our laboratory retrograde labeling phrenic motor neurons with cholera-toxin B fragment in normal rats (Dale-Nagle et al, 2011; Dale et al, 2012; Nichols et al, 2015). Putative phrenic motor neurons were counted as described previously (Nichols et al, 2013a; Nichols et al, 2014), where the area containing phrenic motor neurons was validated and identified as a discrete cluster of large neurons in the mediolateral C 4 ventral horn (Boulenguez et al, 2007; Mantilla, et al, 2009; Watson et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…Bilateral phrenic nerve recordings were made at baseline and during chemoreflex activation in multiple groups, including Harlan rats, wild-type Taconic rats, and end-stage Taconic mutant rats (data obtained from the following studies: Nichols et al, 2013a; 2013b; 2015b). In 6 groups, mean values of integrated phrenic nerve burst peak amplitude were not significantly different between the left and right sides in any group at baseline or during chemoreflex activation (all p>0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Data from some of these groups have appeared in published studies (all studies conducted by N.N. ), and are repeated here to increase the power of our meta-analysis and enable comparisons among rat sub-strains (Nichols et al, 2013a; 2013b; 2015b). …”
Section: Methodsmentioning
confidence: 99%